WAKAMONO KOTOBA PADA IKLAN LINE JAPAN DI YOUTUBE - Bayu Mayanda; Charlina Charlina; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this study is to explain how the formation of Wakamono Kotoba is a type of abbreviation that appears in LINE JAPAN on Youtube. Wakamono Kotoba is said to be a variety of languages created by a particular group or society, used in daily communication processes with meanings that are only known to that group. The implementation of Wakamono Kotoba takes place in real and virtual life, such as digital advertising. Advertising is one type of persuasive discourse that aims to influence listeners or readers, one of which is the LINE JAPAN on Youtube which promotes application digital products in the form of video shows. The method used by researchers in collecting data in this study is the note-taking method. Researchers downloaded 140 LINE JAPAN on Youtube first, then searched, listened and recorded the data found. After that, it is described in the form of a description. The results obtained from this study are that in 140 LINE JAPAN on Youtube, 31 Wakamono Kotoba form of abbreviation.Key Words: Wakamono Kotoba, Abbreviation, LINE JAPAN Commercial